Kontribusi Pendapatan Pembuat Cap Tikus Terhadap Pendapatan Keluarga (Studi Kasus: Petani Cap Tikus di Desa Pinaling Kecamatan Amurang Timur Kabupaten Minahasa Selatan) - Lintjewas, Stedie Richard; Lolowang, Tommy Fredy; Mandei, Juliana Ruth (Sam Ratulangi University, 2023)
The aim of the research is to find out how much income of Cap Tikus maker contributes to family income in Pinaling Village, East Amurang District, South Minahasa Regency. The research was carried out for 4 months, namely November 2022 to February 2023. The research location was in Pinaling Village, East Amurang District, South Minahasa Regency. Primary data was obtained through direct interviews with 15 respondents based on a list of questions, while secondary data was obtained from other sources related to the research. The data analysis method used in this research is descriptive analysis by calculating income and continuing by calculating the contribution of the rat stamp maker's income to family income. The results of this research are (1) The average income of stamp Tikus makers is IDR 3,230,026 (2) The contribution of the stamp mouse maker's income to family income in Pinaling Village, East Amurang District, South Minahasa Regency is 42.10 percent.